La subjectivation de l’agir sexuel violent à l’adolescence : les apports d’un questionnaire d’investigation clinique dans la rencontre de l’adolescent - Pascal Roman; Magali Ravit (Sociétés et Jeunesses en Difficulté, 2011)
A research realized for the Protection judiciaire de la jeunesse (PJJ) in France questions the place of sexual violent acts through adolescence process. One of the questions who mobilised the research’s team concerns the aspects of the adolescent’s meeting with the professionals, in case of sexual infraction, especially in adolescent’s treatment in PJJ’ services.Adolecent’s meeting confront with two difficulties: for the professionals, it is difficult to talk with the adolescents about sexual transgression, and for the adolescents, it’s difficult to recognize self-participation in sexual violent acts as well as self-affective and emotional réaction. In this fact, support of clinical questionnaire (QICAAICS) adapted from the QICPAAS in destination to adolescent people (A. Ciavaldini, 1999), is really interesting. QICAAICS allow to support professional’s and adolescent’s subjectivity. Adolescent‘s subjectivation process will be supported by with the support of professional’s subjectivation process. This support is necessary to meet the adolescents on the scene of intimity opened by sexual transgressions.